The Dog That Didn't Bark : The Strange Case of Domestic Policy Cooperation in the 'New Normal' - Bayoumi, Tamim (IMF Working Papers; Working Paper ;, 2015)
This paper examines domestic policy cooperation, a curiously neglected issue. Both international and domestic cooperation were live issues in the 1970s when the IS/LM model predicted very different external outcomes from monetary and fiscal policies. Interest in domestic policy cooperation has since fallen on hard intellectual times-with knock-ons to international cooperation-as macroeconomic policy roles became highly compartmentalized. I first discuss the intellectual and policy making undercurrents behind this neglect, and explain why they are less relevant after the global crisis. This is followed by a discussion of: macroeconomic policy cooperation in a world of more fiscal activism; coordination across financial agencies and with macroeconomic policies; and how structural policies fit into this. The paper concludes with a proposal for a 'grand bargain' across principle players to create a 'new domestic cooperation.'.